2010
DOI: 10.1016/j.jpain.2009.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Do Past Pain Events Systematically Impact Pain Ratings of Healthy Subjects or Fibromyalgia Patients?

Abstract: We previously reported that three different electronic visual analogue and numerical pain scales are useful in providing refined capacity to discriminate discrete levels of pain intensity. Using the same subjects and scales, we now investigated whether pain scaling is influenced by past pain events and by recalled memories of these events in the rating of pain. Normal control subjects (NC: 19 male; 30 female) and female fibromyalgia (FM) (n = 17) patients received 5 sec suprathreshold heat stimuli (45 -49°C) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Here we characterize the somatosensory, psychological, neurological, and genetic abnormalities of a young child described by her parents as insensitive to pain since birth and compare her to her first‐degree family member and normal controls (NC). Her condition provided the unique opportunity to apply genetic as well as psychological and standardized psychophysical evaluations (Price, 1988; Price and Harkins, 1992; Staud et al, 2010; Price et al, 2008) to precisely characterize the abnormalities associated with her clinical condition. Normal pain‐free controls were used for comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…Here we characterize the somatosensory, psychological, neurological, and genetic abnormalities of a young child described by her parents as insensitive to pain since birth and compare her to her first‐degree family member and normal controls (NC). Her condition provided the unique opportunity to apply genetic as well as psychological and standardized psychophysical evaluations (Price, 1988; Price and Harkins, 1992; Staud et al, 2010; Price et al, 2008) to precisely characterize the abnormalities associated with her clinical condition. Normal pain‐free controls were used for comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…The results, however, also yielded valuable "pain" insight into the life of a middle school student, which can/should be used to build future programs to continue this line of study. Past experiences powerfully influence future experiences and, in this study, having experienced pain more than 3 months powerfully predicted school attendance, PE attendance, recess attendance and sports participation [24,55]. Various studies have shown that school, PE, recess and sports participation/attendance have significant influences on various outcomes including drug use, teen-pregnancy, substance abuse, etc., down the road [7,56].…”
Section: Discussionmentioning
confidence: 55%
“…Likewise, current pain might have had little influence on the change in the appraisal of previous pain experiences in this study. In addition, another study showed that the association between past and current pain could be weak; only a small proportion (26.5%) of individuals without pain used past pain experiences in current pain appraisal (Staud et al, 2010). Contrary to the common assumption that a patient's report is an unreliable source of a pain experience (Marty et al, 2009;Dorfman et al, 2016), these results suggest that it is more accurate than expected, while the risk of being biased by contextual factors remains (Jensen et al, 2008;Boring et al, 2022).…”
Section: Discussionmentioning
confidence: 99%